IMPACT OF CHRONIC ADENOID HYPERTROPHY AND RECURRENT ANTIBIOTIC THERAPY ON COGNITIVE FUNCTION, SLEEP QUALITY, AND HEARING OUTCOMES IN PRESCHOOL CHILDREN – REVIEW - Goździejewska, Wiktoria; Szczygielska , Patrycja; Hejna , Sylwia; Lipiarz , Martyna; Niespodziewański , Michał; Jaworek , Łukasz; Zimka , Gabriela; Bjorgen , Krystian; Jasińska , Lilianna; Roman, Magdalena (International Journal of Innovative Technologies in Social Science, 2026)
In recent years, increasing attention has been paid to the broader developmental consequences of chronic adenoid hypertrophy (AH) in early childhood, particularly in relation to sleep, cognitive performance, and auditory function. Although adenoid enlargement is often regarded as a common pediatric condition, growing evidence indicates that its clinical impact may extend far beyond upper airway obstruction alone. In preschool children, chronic AH is strongly associated with sleep-disordered breathing, recurrent middle ear dysfunction, and repeated courses of antibiotic therapy, all of which may adversely affect critical stages of neurodevelopment. The aim of this review is to analyze the impact of chronic adenoid hypertrophy and recurrent antibiotic therapy on cognitive function, sleep quality, and hearing outcomes in preschool-aged children, with particular emphasis on pathophysiological mechanisms, developmental implications, and current therapeutic approaches. Special attention is given to the relationship between upper airway obstruction and sleep fragmentation, the role of intermittent hypoxia in neurocognitive impairment, and the contribution of adenoid-related Eustachian tube dysfunction to otitis media with effusion and conductive hearing loss. Available evidence indicates that chronic AH may significantly impair sleep architecture, leading to reduced sleep quality, behavioral disturbances, attention deficits, and impaired executive functioning. At the same time, persistent nasopharyngeal obstruction may predispose children to recurrent middle ear disease and fluctuating hearing loss, which in turn can negatively affect speech and language development. Although antibiotic therapy is frequently used in children with recurrent infections associated with AH, its benefits are usually limited to short-term symptom control and do not address the underlying anatomical and functional pathology. Furthermore, repeated antibiotic exposure raises concerns regarding overtreatment and the persistence of disease despite temporary symptomatic improvement. In summary, chronic adenoid hypertrophy should not be considered solely a localized otolaryngological problem but rather a condition with potentially important systemic and developmental consequences. Early diagnosis, careful clinical monitoring, and appropriately selected treatment strategies are essential to reduce the risk of long-term impairment in preschool children.